Performance Analysis of 12Slot with Various Rotor Pole Numbers HE-FSM for HEV Application - Siti Khalidah Rahimi; Zarafi Ahmad; Erwan Sulaiman; Enwelum Mbadiwe I; Syed Muhammad Naufal Syed Othman (Institute of Advanced Engineering and Science, 2017)
This paper presents performance analysis of 12Slot with various rotor pole numbers Hybrid Excitation Flux Switching Machine (HEFSM) for Hybrid Electric Vehicles (HEVs) application. HEFSM has carried out by combining the advantage of Permanent Magnet (PM) machines and DC Field Excitation Coil (FEC) synchronous machines. Previously, most of HEFSM structure having FEC windings in theta direction that create a problem of flux cancellation that will affect the performances of the machine. Thus, a design of 12Slot HEFSM with FEC wounded in radial direction is proposed to eliminate the flux cancellation effect. At first, armature coil arrangement test at no-load condition is conducted to analyze PM flux. Furthermore, induced voltage and cogging torque at open circuit condition are investigated based on 2D finite element analysis (FEA). Finally, torque and power performances are also examined at maximum FEC and armature current densities. The outcomes demonstrate that 12S-14P configuration has the highest PM flux linkage, torque, power and less distortion of back-emf waveform which are required to be used as a motor in HEVs. The highest torque and power achieved are 220.15Nm and 92.45kW, respectively.